2021
DOI: 10.1177/07334648211058718
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Subjective Cognitive Decline in the US

Abstract: Objective The aim of this study was to determine the association between adverse childhood experiences (ACEs) and subjective cognitive decline (SCD) among a representative sample of the adult US population. Methods Data were obtained from the 2019 Behavioral Risk Factor Surveillance System ( N = 82,688, ≥45 years). Adverse childhood experiences included sexual, physical/psychological and environmental ACEs, and a score. Multivariable logistic regression was used to determine the association between ACEs and SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…The third significant discovery of this study is that the DSOA score, which encompasses distress, emotional, and neuroticism scores, is influenced not only by ACEs and NLEs, but also by a subjective perception of cognitive impairments and the RVP_PFA test scores. In this respect, it is interesting to note that a subjective cognitive decline, which is a feature of DSOA, has been linked to ACEs, such as sexual, physical, and psychological abuse (Brown et al, 2022). The RVP_PFA test score is a particular cognitive predictor for DSOA that is not linked to MCI or the severity of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The third significant discovery of this study is that the DSOA score, which encompasses distress, emotional, and neuroticism scores, is influenced not only by ACEs and NLEs, but also by a subjective perception of cognitive impairments and the RVP_PFA test scores. In this respect, it is interesting to note that a subjective cognitive decline, which is a feature of DSOA, has been linked to ACEs, such as sexual, physical, and psychological abuse (Brown et al, 2022). The RVP_PFA test score is a particular cognitive predictor for DSOA that is not linked to MCI or the severity of MCI.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a relationship between ACEs and ADHD diagnosis and severity has been consistently documented (Brown et al, 2022; Crouch et al 2021; Windle et al, 2018); however, the pathophysiological and environmental mechanisms subserving this association are not yet fully understood. Chronic stress, due to repeated exposure to traumatic events, maltreatment, and impoverished environments early in childhood, can alter the trajectory of typical neurodevelopment and has been implicated in the neurobiology of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike with ADHD, there are conflicting results amongst studies exploring the relationship between ACEs and objective cognitive performance. Studies in young adult populations have found that higher number of ACEs have been associated with poorer performance on objective tasks of learning and memory, deficits in executive function (e.g., problem-solving), and reports of higher subjective cognitive difficulties (Brown et al, 2022; Kalia et al, 2021). As people age, ACEs may also be associated with poorer cognitive outcomes (O’Shea et al, 2021).…”
mentioning
confidence: 99%
“…ACEs have been implicated in many mental and physical health outcomes, including sleep, appetite, physical activity, cognitive abilities, and emotional health. [ 1 , 28 - 31 ] Similarly, bullying has been associated with physical health outcomes, including serious injuries, sleep loss, and poor mental health. [ 8 ] While the study aimed not to conflate the two (ACEs and bullying experiences), we wished to highlight that both risk factors are associated with a power differential, are sometimes repetitive, and have been shown to affect the mental health of individuals.…”
Section: Discussionmentioning
confidence: 99%